Three twentieth-century novelists of rural life - ÓDúill, Micheál (Lang, 1992)
Friedrich Griese. - S. 49-92
Includes bibliographical references (p. 186-194) and index
Keywords: Hochschulschrift; Ó Conaire; Pádraic; Genevoix; Maurice; Griese; Friedrich; Pastoral fiction; Rural conditions in literature; Farm life in literature